2015
DOI: 10.1002/cphc.201500713
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition in Ionic Liquids

Abstract: Due to their attractive physico-chemical properties, ionic liquids (ILs) are increasingly used as deposition electrolytes. This review summarizes recent advances in electrodeposition in ILs and focuses on its similarities and differences with that in aqueous solutions. The electrodeposition in ILs is divided into direct and template-assisted deposition. We detail the direct deposition of metals, alloys and semiconductors in five types of ILs, including halometallate ILs, air- and water-stable ILs, deep eutecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
90
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 221 publications
(129 reference statements)
0
90
0
4
Order By: Relevance
“…Metal electroplating from ionic liquids, eutectic formulations and molten salts has been extensively studied in the last years . These non‐aqueous solutions have gained interest because of their non‐volatility and inflammability, good solubility, high stability and their wide electrochemical window .…”
Section: Introductionmentioning
confidence: 99%
“…Metal electroplating from ionic liquids, eutectic formulations and molten salts has been extensively studied in the last years . These non‐aqueous solutions have gained interest because of their non‐volatility and inflammability, good solubility, high stability and their wide electrochemical window .…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical formation of nanostructured materials is a relatively mature field, however, there are consistently new methods and strategies being reported that allow excellent control over composition, size, shape and exposed crystal facets [1][2][3][4][5][6][7]. This is particularly useful given the critical role the aforementioned properties play in electrocatalysis, photocatalysis, surface enhanced Raman spectroscopy and electroanalytical chemistry.…”
Section: Introductionmentioning
confidence: 97%
“…1ashows linear sweep voltammograms for the electroreduction of PtCl6 2− ions in the absence (black line) and presence (red line) of Pt nanoparticles. In the absence of nanoparticles in the electrolyte, two distinct reduction peaks are observed at ca.…”
mentioning
confidence: 99%
“…Although both of these techniques are very promising and are strongly pursued in laboratories worldwide, their use on a large scale is still limited. Ionic liquids are mainly used to deposit metals with a Nernst potential below that of water decomposition and, therefore, cannot be electroplated from aqueous baths [37][38][39]. The most common example is the electrodeposition of aluminum.…”
Section: Introductionmentioning
confidence: 99%